2020
DOI: 10.18100/ijamec.801730
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Conducted EMI in SiC Based Dual Active Bridge Converter

Abstract: Power converters are required to work faster and with higher power density with the developing technology. Therefore, the converter is expected to work in more than one direction. Usage of Dual Active Bridge DC-DC Converter is an example. To increase the power density of the converters, it is necessary to increase the switching frequency. In conventional Si MOSFET based converters, power losses are very high and cause high electromagnetic interferences at high frequencies. These disadvantages lead developers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There are two types of electromagnetic interference (EMI) propagation types. The first of these is emission by radiation, which the EMI source interferes with through the air [4][5][6][7][8][9][10], and the second is the emission by transmission, where the source interferes over the line to which it is connected [11,12]. The form of conducted emission noise is defined by modes in systems.…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of electromagnetic interference (EMI) propagation types. The first of these is emission by radiation, which the EMI source interferes with through the air [4][5][6][7][8][9][10], and the second is the emission by transmission, where the source interferes over the line to which it is connected [11,12]. The form of conducted emission noise is defined by modes in systems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that SiC Mosfet emits EMI at high frequencies, but it is less than Si Mosfet . [2] There are studies on how the This study was carried out to compare the Silicon (Si) and Silicon Carbide (SiC) MOSFETs in the market used on motor driver circuits. A motor driver circuit is designed to run the Brushless Digital Current motors.…”
Section: Introductionmentioning
confidence: 99%